Integrasi Flipped Classroom dengan Inkuiri Terbimbing Berbasis Literasi Digital Menggunakan Discord pada Materi Kinetika Kimia untuk Mahasiswa Kimia Tahun Pertama - Mega Sofyan; Reza Akmar; Mawardi Mawardi; Alizar Ulianas; Okta Suryani (Jurnal Penelitian Pendidikan IPA, 2025)
To response the needs for 21st century competencies among chemistry students, a novel approach on learning in higher education is paramount. This study presents the development and evaluation of a flipped classroom learning system for chemical kinetics, designed to enhance digital literacy and guided inquiry through Discord. This research followed the Educational Design Research (EDR) model outlined by Plomp and Nieveen and limited to development studies; yielding  a refined learning system prototype. The developed learning system was validated by five lecturers from Universitas Negeri Padang, resulted in content (0.85), and construct validity (0.82). Meanwhile, the practicality of the learning system was also evaluated by students and lecturers, resulted in practicality indexes of 88% and 85%, respectively. All of the results suggest high level of validity and practicality meaning the learning system has achieved the quality criteria content, structure, and usage wise. These results imply for the utilization platforms like Discord for higher education learning to promote student-centered learning and digital literacy.